THE INVERSE OF OPERATOR MATRIX A WHERE A≥I - Balasim, Mohammed (Iraqi Journal of Science, 2024)
Let H and K be Hilbert spaces and let H K be the cartesian product of them.LetB(H),B(K),B(H  K),B(K,H),B(H,K) be the Banach spaces of bounded(continuous)operators on H,K,H K,and from K into H and from H into K respectively. In thispaper we find the inverse of operator matrixD EB CA B(H K) whereBB(H) ,CB(K,H), DB(H,K), EB(K) and A≥ H K I  where H K I  is theidentity operator on H K.